Sleep habits as predictors of psychological health in healthcare professionals - Díaz-Ramiro, Eva María; Rubio-Valdehita, Susana; López-Núñez, Maria Inmaculada; Aparicio-García, Marta Evelia (Anales de Psicología / Annals of Psychology, 2020)
The aim was to study the sleep habits and the psychological health of professionals in the health sector, as well as to analyze the relationships between both variables. The sample consisted of 511 workers from public hospitals in the Community of Madrid. Psychological health was evaluated using the GHQ-28 Questionnaire; and sleep habits with the CHAS Questionnaire. In addition, sociodemographic data were collected, such as age, sex, job position, professional category. The results showed statistically significant differences in somatic symptoms, psychological health and stability in sleep habits. Regression analysis indicated that sleep quality and daytime sleepiness are the variables most related to health dimensions, especially with anxiety/insomnia and somatic symptoms. These results reveal the differences between sleep habits and perceived health in nursing staff and physicians. Finally, the health workers present a higher prevalence of psychological distress, and poor sleep quality and instability in sleep hours. Sleep impairment, somnolence and somatic symptoms are more frequent in nursing staff than in other health professionals.